PENDAMPINGAN BIMBINGAN BELAJAR TATAP MUKA TERBATAS MASA PANDEMI COVID 19 DI DESA EKOROKA KECAMATAN GOLEWA KABUPATEN NGADA - Renata Rita Rosana Lado; Maria Jaa; Pelipus Wungo Kaka (STKIP Citra Bakti, 2022)
Education in Indonesia is currently still experiencing problems in various aspects. One of them is the low quality of education due to the current covid 19 pandemic situation that does not carry out face-to-face learning to avoid the spread of the corona virus. Learning that is actually carried out face-to-face must be done online because of the pandemic. Face-to-face tutoring limited to the covid 19 pandemic in the afternoon is one of the efforts to add insight to learners. Students of KKN STKIP Citra Bakti carry out thematic KKN with the concept of free learning one of which is by conducting tutoring. Tutoring conducted in accordance with their respective study programs is one form of the implementation of one of the tri darma in college, namely devotion. Tutoring is carried out in the afternoon and the target is students / students from SDI Rutosoro domiciled in Ekoroka Village. The method used is (diffusion) which is to produce products for the target group, (Training) which is an activity accompanied by demonstrations or pilots to produce certain skills and (Advocacy) which is an activity in the form of assistance to the target group.The results of tutoring activities carried out are students are very enthusiastic and active in guidance activities as well as skilled in using props and very active in singing. Tutoring in the afternoon in the time of the covid 19 pandemic is very important to add insight to learners.Tutoring assistance activities in the covid-19 pandemic period aim to improve student understanding and increase the insight of learners due to the lack of intensity of teacher and student meetings.